Molecular features of colorectal polyps presenting Kudo’s type II mucosal crypt pattern: are they based on the same mechanism of tumorigenesis? - Shinmura, Kensuke; Konishi, Kazuo; Yamochi, Toshiko; Kubota, Yutaro; Yano, Yuichiro; Katagiri, Atsushi; Muramoto, Takashi; Kihara, Toshihiro; Tojo, Masayuki; Konda, Kenichi; Tagawa, Teppei; Yanagisawa, Fumito; Kogo, Mari; Makino, Reiko; Takimoto, Masafumi; Yoshida, Hitoshi (Endoscopy International Open, 2014)
Background and study aims: The molecular features of serrated polyps (SPs) with hyperplastic crypt pattern, also called Kudo’s type II observed by chromoendoscopy, were evaluated.Methods: The clinicopathological and molecular features of 114 SPs with a hyperplastic pit pattern detected under chromoendoscopy (five dysplastic SPs, 63 sessile serrated adenoma/polyps (SSA/Ps), 36 microvesicular hyperplastic polyps (MVHPs), and 10 goblet cell-rich hyperplastic polyps (GCHPs)) were examined. The frequency of KRAS and BRAF mutations and CpG island methylator phenotype (CIMP) were investigated.Results: Dysplastic SPs and SSA/Ps were frequently located in the proximal colon compared to others (SSA/Ps vs. MVHPs or GCHPs, P < 0.0001). No significant difference was found in the frequency of BRAF mutation among SPs apart from GCHP (60 % for dysplastic SPs, 44 % for SSA/Ps, 47 % for MVHPs, and 0 % for GCHPs). The frequency of CIMP was higher in dysplastic SPs or SSA/Ps than in MVHPs or GCHPs (60 % for dysplastic SPs, 56 % for SSA/Ps, 32 % for MVHPs, and 10 % for GCHPs) (SSA/Ps vs. GCHP, P = 0.0068). When serrated neoplasias (SNs) and MVHPs were classified into proximal and distal lesions, the frequency of CIMP was significantly higher in the proximal compared to the distal SNs (64 % vs. 11 %, P = 0.0032). Finally, multivariate analysis showed that proximal location and BRAF mutation were significantly associated with an increased risk of CIMP.Conclusions: Distinct molecular features were observed between proximal and distal SPs with hyperplastic crypt pattern. Proximal MVHPs may develop more frequently through SSA/Ps to CIMP cancers than distal MVHPs.